Management of adrenocortical carcinoma - Allolio, Bruno; Hahner, Stefanie; Weismann, Dirk; Fassnacht, Martin (Clinical endocrinology (Oxford), 2004)
Summary Adrenocortical carcinoma (ACC) is a rare neoplasm with poor prognosis. Patients present with signs of steroid hormone excess (e.g. Cushing's syndrome, virilization) or an abdominal mass. Tumour size at presentation (mean diameter at diagnosis > 10 cm) is the most important indicator of malignancy. In addition, computed tomography (CT) typically demonstrates an inhomogeneous adrenal lesion with irregular margins and variable enhancement of solid components after intravenous contrast media. Magnetic resonance imaging (MRI) is equally effective as CT and is particularly helpful to visualize invasion into large vessels. Complete tumour removal (R0 resection) offers by far the best chance for long‐term survival and therefore surgery is the treatment of choice in stage I–III ACC. Despite tumour resection for cure most patients will eventually develop local recurrence or distant metastases. Thus adjuvant treatment options need to be evaluated in high‐risk patients (e.g. radiation therapy of the tumour bed and/or chemotherapy). In tumour recurrence re‐operation should always be considered. In metastatic disease (stage IV ACC) not amenable to surgery mitotane (o,p′DDD) remains the first‐line therapy. Drug monitoring is needed for effective treatment aiming at concentrations between 14 and 20 mg/l. Patients not responding to mitotane may benefit from cytotoxic chemotherapy (23% partial remissions, 4% complete remissions). Only large prospective multicentre trials comparing different treatment options will allow to make systematic progress in the management of ACC.